Особливості управління великими даними через мультитенантні хмарні системи - Сердюк, Н. М.; Вольгуст, М. С. (ХНУРЕ, 2025)
Modern intelligent manufacturing systems face challenges related to processing large volumes of data in real-time. One of the promising approaches is the use of a multitenant cloud architecture, which ensures high performance, reliability, and adaptability to variable workloads. This paper proposes an architectural model that integrates containerization (Docker), orchestration (Kubernetes), and intelligent data analysis. The proposed system has been tested, and its effectiveness has been proven in the context of cyber-physical manufacturing environments.
Keywords: хмарна система; мультитенантна архітектура